Knowledge management and e-government in Brazil - Knight, Peter T. ([s.n.] [S.l.], 2007)
Reviews the state of knowledge management (KM) policy adoption in Brazil's federal government and the state of Sao Paulo. Concludes with a brief description of the e-Brasil project, which promotes public policies to make intensive use of information and communication technologies to accelerate Brazil's socioeconomic developmenet.